2018
DOI: 10.1039/c8cc05425h
|View full text |Cite
|
Sign up to set email alerts
|

Biotin-tagged fluorescent sensor to visualize ‘mobile’ Zn2+ in cancer cells

Abstract: A cancer cell-targeting fluorescent sensor has been developed to image mobile Zn2+ by introducing a biotin group. It shows a highly selective response to Zn2+in vitro, no toxicity in cellulo and images 'mobile' Zn2+ specifically in cancer cells. We believe this probe has the potential to help improve our understanding of the role of Zn2+ in the processes of cancer initiation and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The restriction of intramolecular rotations can also hinder the access to low energy conical intersections associated with ultrafast decay to the ground state. This theory was used to explain similar previous findings by us 6,22,31 and has been discussed elsewhere. 33,34…”
Section: Dft Calculationsmentioning
confidence: 64%
See 2 more Smart Citations
“…The restriction of intramolecular rotations can also hinder the access to low energy conical intersections associated with ultrafast decay to the ground state. This theory was used to explain similar previous findings by us 6,22,31 and has been discussed elsewhere. 33,34…”
Section: Dft Calculationsmentioning
confidence: 64%
“…The trityl protected probe 1 was then readily obtained by stepwise double 'click' reactions following our originally reported procedures. 31 Although the deprotected probe 2 was ultimately ineffective in cellulo, as expected, it was also isolated for further characterization and testing in vitro. All products were satisfactorily characterized by 1 H, 13 C NMR and IR spectroscopies, as well as high-resolution mass spectrometry.…”
Section: Synthesis and Characterizationmentioning
confidence: 68%
See 1 more Smart Citation
“…In 2018, we developed the biotinylated probe 34 based on 1,8-naphthalimide moiety for imaging Zn 2+ in breast cancer MCF-7 cells and found it has nuclear envelope penetrability. 90 However, it suffers from the same issue as 33 in that it was distributed over the entire cell and its sensitivity was insufficient to detect endogenous nuclear Zn 2+ with the nucleus uorescence only being switched on aer the addition of exogenous Zn 2+ .…”
Section: Nucleus Targetingmentioning
confidence: 99%
“…To date, considerable effort has been devoted to the development of Zn 2+ probes. [11][12][13][14][15][16][17][18][19][20] Fluorescence-based systems have received particular attention in this regard since they provide good sensitivity, selectivity, and spatial and temporal resolution. In 2010, Lippard, et al reported the uorescence Zn 2+ probe, ZPP1, which was successfully used to identify PCa in a transgenic mouse model.…”
Section: Introductionmentioning
confidence: 99%